2017
DOI: 10.29136/mediterranean.360013
|View full text |Cite
|
Sign up to set email alerts
|

Türkiye’de satışa sunulan arı sütlerinin kimyasal özellikleri

Abstract: Although the consumption of royal jelly has been rapidly increased in recent years, there is a lack of knowledge about the quality of commercial royal jelly purchased in Turkey. In order to evaluate quality properties, a total of thirteen different royal jelly samples, consisting of 12 commercial samples in Turkish markets, and 1 sample of known origin obtained freshly harvested from honeybee colony in Akdeniz University were analyzed for water, crude protein, acidity, pH, ash, total sugar, fructose, glucose, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…(2020) determined that the quantity of 10‐HDA in 105 samples of RJ from different years ranged between 2.1 % and 2.6 % on average [32] . Also, Yavuz and Gürel (2017) reported that the 10‐HDA content of commercial samples of RJ varied from 0.75 to 3.11 percent [37] . The decreasing and low value of 10‐HDA in RJ can be associated with decomposition, poor quality, and adulteration [38] .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(2020) determined that the quantity of 10‐HDA in 105 samples of RJ from different years ranged between 2.1 % and 2.6 % on average [32] . Also, Yavuz and Gürel (2017) reported that the 10‐HDA content of commercial samples of RJ varied from 0.75 to 3.11 percent [37] . The decreasing and low value of 10‐HDA in RJ can be associated with decomposition, poor quality, and adulteration [38] .…”
Section: Resultsmentioning
confidence: 99%
“…[32] Also, Yavuz and Gürel (2017) reported that the 10-HDA content of commercial samples of RJ varied from 0.75 to 3.11 percent. [37] The decreasing and low value of 10-HDA in RJ can be associated with decomposition, poor quality, and adulteration. [38] From this perspective, it was seen that the 10-HDA average depending on the year the samples were obtained (2.39 % in 2018, 2.16 % in 2019, and 2.41 % in 2020) was higher than the required values.…”
Section: Resultsmentioning
confidence: 99%